Determinants of patient satisfaction in branded hospital - Jayakrishnan, J.; Solayappan, A.; Kumaran, C. (university of Jaffna, 2014)
Patient satisfaction in a hospital is basically a state of mind of the patient. It is the ability of the hospital service to meet the expectations of the patient. Patient delight is all about exceeding the expectations of the patients to make them highly satisfied with the hospital. In hospital perspective, customer is any individual or institution who is an actual, potential or future user of the hospital and its various services. The customer from the hospital is very different from the regular customer, the difference being that they do not want to be a customer in the first place. The hospital customer is forced to be a customer because of their illness and parts with their money unhappily.
Keywords: Satisfaction; Mind; Ability